Assessment of Obesity, Dyslipidemia, Hyperglycemia, and Pro-Inflammatory Cytokines as Cardiovascular Disease Risk Factors in Acromegaly Patients (Baghdad Science Journal, 2022)
Cardiovascular disease is one of the most common comorbidities associated with enlarged extremities, occurring in 60 % of patients with acromegaly. The aim of this study is to evaluate the relationship of growth hormone and insulin such as growth factor-1 with obesity, dyslipidemia, hyperglycemia, and pro-inflammatory cytokines (IL-2, IL-6, IL-10), as risk factors for cardiovascular disorder in acromegaly patients. Eighty subjects were included and categorized into two groups: 40 acromegaly patients and 40 of the control group. The results indicated weight excess, hyperglycemia, hypertension, lipid disorder, and elevated levels of interleukins (2, 6, and 10). The correlation of both GH and IGF-1 with each of weight, BMI, systolic blood pressure, diastolic blood pressure, FBS, HbA1c, cholesterol, triglyceride, LDL, IL6, IL2, and the atherogenic index was found to be positive and significant. Meanwhile, only IGF-1 was significantly correlated with IL10. We conclude that elevated levels of IL2, IL6, IL 10 and their association with both GH and IGF-1 as well as to lipid disorder, hyperglycemia, and hypertension criteria of acromegaly patients are all risk factors for cardiovascular disease, suggesting the necessary clinical examination for cardiovascular disorder in patients with acromegaly patients.